1969
DOI: 10.1029/ja074i009p02161
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of solar protons to synchronous altitude

Abstract: Solar proton fluxes in two energy intervals (5–21 Mev and 21–70 Mev) were measured with detectors aboard the geostationary ATS 1 satellite during the solar proton event that began on January 28, 1967. Comparison with data obtained by satellites outside the magnetosphere shows that (a) protons with energies greater than 21 Mev have essentially free access to synchronous altitude; (b) protons in the 5–21 Mev energy interval show a diurnal variation with the flux approaching the interplanetary flux level near loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 17 publications
(12 reference statements)
0
35
0
Order By: Relevance
“…For each of the peaks in SEPs, there is a corresponding peak in the proton flux at GEO on the same day. The higher energy fluxes (0.74-14.5 MeV) studied here are all controlled mainly by the SEP, which was established in the 1960s (Paulikas and Blake, 1969). For the 0.74-4.2 MeV protons, the SEP flux is coupled with the velocity, which suggests that higher solar wind speed could increase the access of the SEPs.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…For each of the peaks in SEPs, there is a corresponding peak in the proton flux at GEO on the same day. The higher energy fluxes (0.74-14.5 MeV) studied here are all controlled mainly by the SEP, which was established in the 1960s (Paulikas and Blake, 1969). For the 0.74-4.2 MeV protons, the SEP flux is coupled with the velocity, which suggests that higher solar wind speed could increase the access of the SEPs.…”
Section: Discussionmentioning
confidence: 90%
“…Paulikas and Blake (1969), using data from GEO satellite ATS 1 and measurements from outside the magnetosphere, showed that during magnetically quiet times, protons with energies > 20 MeV have free access to the geosynchronous regions of the magnetosphere as the theory suggested. However, the energies lower 20 MeV were also shown to have access to the magnetosphere, in contrast to the theories at the time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIP's and AIP's, which are more associated with auroral events (3.1), could be related to the electron precipitation which occurs during substorms. Direct access of solar protons (E> 2 MeV) to the magnetosphere during substorms (Martinides and Taorini, 1968;Paulikas and Blake, 1969) could also play a role in the generation mechanism of ULF pulsations.…”
Section: Resultsmentioning
confidence: 99%
“…This monotonicity suggests inward radial diffusion from an outer boundary at L 1 10 but does not prove that the particles maintaining the boundary condition originate outside the earth's magnetosphere. Many particles clearly do originate one or more astronomical units from the earth, e.g., solar-flare protons seen at synchronous altitude within hours after the flare [Paulikas and Blake, 1969]. One of the provoca- [1979] that relativistic electrons from Jupiter's magnetosphere [e.g., Krimigis et al, 1975;Iewaldt et al, 1976] help to populate the earth's outer zone at energies 4 5 HeV.…”
Section: Itroduct Ion'mentioning
confidence: 99%